Cardiac dysfunction in patients with end stage liver disease, incidence and impact on outcome - Mohammed Rabie Anwar; Fatma Mohammed Nasr; Hatem Hamed Alatroush; Khaled Hussein Mohammed (Cairo : Mohammed Rabie Anwa, 2018)
Background: Without firm diagnostic criteria, the exact prevalence of cirrhotic cardiomyopathy remains unknown. Its estimation is a difficult task as the disease is generally latent and shows itself only when the patient is subjected to stress such as body position changes, exercise, drugs, hemorrhage and surgery. Aim of the Work: to assess cardiac dysfunction in patients with end-stage liver disease, study the correlation between cardiac dysfunction and CHILD classification of patients with liver cell failure and study the incidence and impact of cardiac dysfunction on the clinical outcome of patients with CHILD B and CHILD C liver disease. Patients: and Methods: This comparative prospective case control study was conducted on 40 non-alcoholic liver cirrhosis patients with end stage liver disease, admitted in the intensive care unit in Theodor Bilharz Research Institute within one year from August 2016 to August 2017 with ECG and Echo Doppler with TDI done in patients and controls. Results: Most of patients had cardiac dysfunction mainly diastolic dysfunction in 87.5%. No correlation was found between cardiac dysfunction and severity of hepatic illness with severity of hepatic illness affecting the outcome rather than cardiac dysfunction
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Cardiac dysfunction; End stage liver disease; Outcome